FACTORS ASSOCIATED WITH EXCLUSIVE BREASTFEEDING FOR BABIES DURING THE COVID-19 PANDEMIC IN THE TAMALANREA JAYA HEALTH CENTER WORK AREA MAKASSAR CITY - Cindy Dwi Lestari; Jalil Genesis; Sri Handayani (Ikatan Sarjana Gizi Indonesia (ISAGI), 2023)
Mother's Milk (ASI) is the best primary food for babies, especially during the Covid-19 pandemic because it contains many nutrients and antibodies to increase the baby's immune system and exclusive breastfeeding is very important for babies for optimal baby growth and development. The purpose of this study was to determine the correlation between mother's knowledge, mother's occupation, and family support with exclusive breastfeeding for infants during the Covid-19 pandemic in the working area of ​​the Tamalanrea Jaya Health Center Makassar City. This research is quantitative by using the Cross-Sectional Study method with an analytical survey design. The sampling technique used purposive sampling with a total of 49 respondents. The research instrument used a questionnaire and test Chi-Square. The results showed that exclusive breastfeeding for infants was based on the test Chi-Square it was found that there was a significant correlation between the mother's knowledge and exclusive breastfeeding (p-value 0.013 < 0.05), there was a significant correlation between the mother's work and exclusive breastfeeding (p-value 0.008 < 0.05), and there was a significant correlation between family support. with exclusive breastfeeding (p-value 0.041 < 0.05). The conclusion is that there is a significant correlation between the mother’s knowledge, the mother’s occupation, and family support with exclusive breastfeeding for babies during the Covid-19 pandemic. The suggestion is that it is hoped that mothers continue to explore information about the importance of the benefits of exclusive breastfeeding for babies during the Covid-19 pandemic by implementing health protocols and mothers to be more active in conducting examinations during pregnancy to obtain information related to exclusive breastfeeding.